Forensic Investigation and Fraud Prevention in the Nigerian Deposit Money Banks - Adu Cecilia Adurayemi; Oke-Potefa Oladele Sewanu; Sadiq Moshood Obasanjo; Abdulkaffel Safiyat Lami (International Journal of Global Sustainable Research, 2025)
This study investigated forensic investigation and fraud control in Nigerian deposit money banks (DMBs). An organized questionnaire was utilized to collect the necessary data from the respondents for the study, which used a descriptive survey methodology. Key staff of the deposit money banks in the Nigerian states of Lagos and Ogun made up the population. The research revealed that fraud control was significantly impacted by forensic fraud investigation. The study concluded that forensic investigation enhanced the control of fraud in the deposit money banks in Nigeria. In order to combat fraud, the study suggested that DMBs should strengthen their forensic investigation practices. This could be accomplished by routinely and consistently doing forensic audits of financial documents. DMBs should also make sure that any staff members engaging in fraud were promptly investigated and prosecuted